(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article presents some results of the modeling of the bag-like aneurysm by the finite element method. The model takes into account the specificity of the blood flow from the point of view of various rheological models, as well as a significant change in the shape of the saccular aneurysm depending on pressure.